Analysis of the Realistic Mathematics Education Approach and Its Influence on Critical Thinking Skills - Harman Harman (International Journal of Multidisciplinary Sciences and Arts, 2025)
The purpose of this study is to balance the ineffectiveness of classroom learning in the learning process with conventional models, while students who receive it are more passive and afraid to express their opinions because they consider mathematics difficult to learn. This study uses an experimental quantitative research method. The population in this study were all students of grade VII. Sampling using the Random Sampling technique, where two classes were given different treatments. The results of this study are to determine the differences in the Realistic Mathematics Education (RME) approach to the critical thinking skills of seventh-grade students of SMPN 2 Kota Jambi. Based on the results of the Post-test, it can be seen that the critical thinking skills of students in class VIIIA (experimental) of SMP Negeri 2 Kota Jambi on the material set, the average value is 76.84 with a standard deviation of 6.96 while in class VIIID (Control) the average is 72.75 with a standard deviation of 11.64. Based on this calculation there is a difference between the experimental class and the control class, this is the influence of the Realistic Mathematics Education (RME) approach.